Gamma Interferon-Independent Effects of Interleukin-12 on Immunity to Salmonella enterica Serovar Typhimurium - Price, Jason D. (American Society for Microbiology (ASM), 2007)
Interleukin-12 (IL-12) and IL-18 are both central to the induction of gamma interferon (IFN-γ), and various roles for IL-12 and IL-18 in control of intracellular microbial infections have been demonstrated. We used IL-12p40(−/−) and IL-18(−/−) mice to further investigate the role of IL-12 and IL-18 in control of Salmonella enterica serovar Typhimurium. While C57BL/6 and IL-18(−/−) mice were able to resolve attenuated S. enterica serovar Typhimurium infections, the IL-12p40(−/−) mice succumbed to a high bacterial burden after 60 days. Using ovalbumin (OVA)-specific T-cell receptor transgenic T cells (OT-II cells), we demonstrated that following oral infection with recombinant S. enterica serovar Typhimurium expressing OVA, the OT-II cells proliferated in the mesenteric lymph nodes of C57BL/6 and IL-18(−/−) mice but not in IL-12p40(−/−) mice. In addition, we demonstrated by flow cytometry that equivalent or increased numbers of T cells produced IFN-γ in IL-12p40(−/−) mice compared with the numbers of T cells that produced IFN-γ in C57BL/6 and IL-18(−/−) mice. Finally, we demonstrated that removal of macrophages from S. enterica serovar Typhimurium-infected C57BL/6 and IL-12p40(−/−) mice did not affect the bacterial load, suggesting that impaired control of S. enterica serovar Typhimurium infection in the absence of IL-12p40 is not due to reduced macrophage bactericidal activities, while IL-18(−/−) mice did rely on the presence of macrophages for control of the infection. Our results suggest that IL-12p40, but not IL-18, is critical to resolution of infections with attenuated S. enterica serovar Typhimurium and that especially the effects of IL-12p40 on proliferative responses of CD4(+) T cells, but not the ability of these cells to produce IFN-γ, are important in the resolution of infection by this intracellular bacterial pathogen.